Optimizing seed injection as a seagrass restoration method. Issue 3 (22nd December 2022) - Gräfnings, Max L. E.; Heusinkveld, Jannes H. T.; Hoeijmakers, Dieuwke J. J.; Smeele, Quirin; Wiersema, Henk; Zwarts, Maarten; van der Heide, Tjisse; Govers, Laura L.
Abstract : Due to the major declines of seagrasses worldwide, there is an urgent need for effective restoration methods and strategies. In the Dutch Wadden Sea, intertidal seagrass restoration has proven very challenging, despite numerous restoration trials with different restoration methods. Recently, however, the first field trial performed with a newly developed "dispenser injection seeding" method (DIS) resulted in record‐high plant densities and seed recruitment. Here, we present the further development of the methodology and consequently improved restoration results. During two consecutive growing seasons, we honed the seeding technique and experimentally investigated how seeding depth (2/4 cm), injection density (25/100 injects/m 2 ), and seed amount (2/20 seeds/inject) affected restoration of intertidal annual Zostera marina . We found that all variables had a significant impact on plant establishment. Seeding deeper (4 cm) had the largest positive effect on restored plant densities, while lowered seed densities (2 seeds/inject) had the largest positive impact on seed recruitment. The optimized DIS method, combined with an altered placement of the seeding hole, resulted in a 50‐fold increase in restored plant densities (from approximately 1 to 57 plants/m 2 ) and a simultaneous increase in seed recruitment (from 0.3 to 11.4%). These improvements stem from the method's ability to counteract a recruitment bottleneck, where seeds are lost through hydrodynamic forcing. The methodological improvements described here are important steps toward restoring self‐sustaining seagrass populations in the future and our study demonstrates the high potential of the seed‐based DIS method for seagrass restoration.